2018
DOI: 10.1093/jac/dky187
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for azole resistance in clinical and environmental isolates of Aspergillus fumigatus in Australia and cyp51A homology modelling of azole-resistant isolates

Abstract: Azole resistance is uncommon in Australian clinical and environmental A. fumigatus isolates; further surveillance is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
0
28
2
2
Order By: Relevance
“…While time efficient, these commercial assays are limited by the fact that CYP51A is a single copy gene, and that they detect only azole resistance involving the tandem repeat. In Australia where the incidence of azole resistance is low (< 3%), 2/3 azole resistant isolates had the G54R mutation associated with high MICs to itraconazole and posaconazole (Talbot et al, 2018). A recent study from the United Kingdom employing the AsperGenius assay R (PathoNostics BV) showed that 16/22 (73%) isolates with the resistant phenotype harbored no mutations detected by this test (Abdolrasouli et al, 2018).…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 99%
“…While time efficient, these commercial assays are limited by the fact that CYP51A is a single copy gene, and that they detect only azole resistance involving the tandem repeat. In Australia where the incidence of azole resistance is low (< 3%), 2/3 azole resistant isolates had the G54R mutation associated with high MICs to itraconazole and posaconazole (Talbot et al, 2018). A recent study from the United Kingdom employing the AsperGenius assay R (PathoNostics BV) showed that 16/22 (73%) isolates with the resistant phenotype harbored no mutations detected by this test (Abdolrasouli et al, 2018).…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 99%
“…Countries reporting the presence of azole-resistant Aspergillus fumigatus and mechanisms of resistance in surveyed isolates [47,48,49,52,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97]. …”
Section: Figurementioning
confidence: 99%
“…In addition, given the limited availability of antifungal drugs to treat fungal infections, this increase in resistance rates found in clinical practice poses a substantial problem and could result in treatment failure and a consequent increase in mortality rates [99]. Current local azole resistance rates vary between 0 and 26%, variation occurring according to geographic region and patient population [86,91,97,[100][101][102][103][104][105][106]. An investigation, involving 13 countries in four continents, found an azole resistance rate of 6% among 2026 Aspergillus isolates evaluated [107].…”
Section: Aspergillus Azole Resistancementioning
confidence: 99%
“…Point mutations as G54 and M220 can change the protein structure, which affects the docking of certain azole compounds for the whole protein [114][115][116]. On the other hand, mutations such as TR 34 /L98H, which confers pan-azole resistance [100,101], and TR 46 /Y121F/T289A, apparently more related to a high level of voriconazole resistance and variable susceptibility to itraconazole [114,117,118], are reported in environmental strains [101,119], in patients with long-term treatment as well as in patients with IA [90,106,120,121].…”
Section: Main Mechanisms Of Azole Resistancementioning
confidence: 99%